2008
DOI: 10.1007/s00421-008-0836-1
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise effects on blood glutathione status and plasma protein carbonyls: influence of partial vascular occlusion

Abstract: Seven weight-trained males performed both light resistance with partial occlusion (LRO: 30% 1 RM) and moderate resistance (MR: 70% 1 RM) to failure to ascertain whether blood protein carbonyls (PC) and glutathione status was altered compared to partial occlusion (PO) in a counterbalanced fashion. PO was identical in duration to the LRO session and all sessions were on separate days. PC did not differ for the three conditions at PRE (0.05 nM mg protein(-1)). PC significantly increased for PO and MR over time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 25 publications
(47 reference statements)
3
92
0
5
Order By: Relevance
“…However, while the activity of ROS within muscle is known to increase in ischemic conditions, particularly upon reperfusion [84], previous research by Takarada et al [8] reported no change in lipid peroxide levels following lowintensity resistance exercise either with or without BFR. Similar findings were reported by Goldfarb et al [85], who observed no significant increase in markers of oxidative stress (glutathione status and plasma protein carbonyls) following lowintensity (30% 1RM) resistance exercise with BFR, despite increases following both moderate-intensity (70% 1RM) resistance exercise without BFR, and BFR alone. As such, further research is required to investigate whether markers of redox signalling and exercise-induced ROS production are augmented by the addition of BFR, and if ROS play a role in subsequent cellular signalling processes for post-exercise muscle adaptations [64].…”
Section: Intramuscular Signallingsupporting
confidence: 90%
“…However, while the activity of ROS within muscle is known to increase in ischemic conditions, particularly upon reperfusion [84], previous research by Takarada et al [8] reported no change in lipid peroxide levels following lowintensity resistance exercise either with or without BFR. Similar findings were reported by Goldfarb et al [85], who observed no significant increase in markers of oxidative stress (glutathione status and plasma protein carbonyls) following lowintensity (30% 1RM) resistance exercise with BFR, despite increases following both moderate-intensity (70% 1RM) resistance exercise without BFR, and BFR alone. As such, further research is required to investigate whether markers of redox signalling and exercise-induced ROS production are augmented by the addition of BFR, and if ROS play a role in subsequent cellular signalling processes for post-exercise muscle adaptations [64].…”
Section: Intramuscular Signallingsupporting
confidence: 90%
“…This finding is critical considering the importance of a compressed training duration and, to an extent, training frequency, which was discussed above and appears central to KAATSU low-intensity training. The ability to compress the training duration is certainly related to the use of low-intensity exercise, which does not appear to cause significant muscle damage or delayed recovery, as indicated by a lack of change in the blood markers of muscle damage or immune stress (Fujita et al, 2008;Goldfarb et al 2008;Takarada et al, 2000), while still promoting muscle adaptations. Further, the average reported score for intensity and discomfort (including pain) for all participants was 11-14 on a scale of 6-20, using the Borg RPE Scale (Borg, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…BFR training research typically employs training volumes ranging from 45 [13] to 75 [55] repetitions each exercise per session. Several investigations have utilized BFR combined with lowload resistance exercise to volitional fatigue [4,65,66]. However, exercise to failure is not submaximal by definition, and therefore may not be appropriate for many clinical populations who would otherwise benefit from BFR training [67].…”
Section: Training Volumementioning
confidence: 99%